UPAYA MENINGKATKAN APRESIASI SASTRA MURID KELAS V SD NEGERI 4 SESETAN DENPASAR PADA BACAAN CERITA MELALUI LOKAKARYA MEMBACA - I Ketut Adnyana Putra (Jurnal Santiaji Pendidikan (JSP), 2011)
This class action research's objective is to develop the students literature appreciation year 5, to the story reading through reading workshop which focus on the developing of emotive response to the content of the story and the developing response at the character and event in the story. This research took place at SD 4 Sesetan Denpasar in two cyclus, in every cycle hare are two meeting. This subject research is year 5 teacher. The research data is collected using observation, interview, and document analyzing technique. The data is analyzed qualitatively which refers to ongoing analysis principle. The result of the research Indicates that through reading workshop activity, rind the. procedure (1) mini lessons, that is introduction of the story book, selection of the story books based on the student’s interest, (2) continued to the silent residing, (3) making dialogue journal, and at last (4) sharing, literature appreciation students year 5 elementary school to the story reading covers emotive response to the story contents, and the response to the character and event at the story develop.